Chemical Optimization Algorithm for Fuzzy Controller Design - Astudillo, Leslie; Melin, Patricia; Castillo, Oscar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
In this book, a novel optimization method inspired by a paradigm from nature is introduced. The chemical reactions are used as a paradigm to propose an optimization method that simulates these natural processes. The proposed algorithm is described in detail and then a set of typical complex benchmark functions is used to evaluate the performance of the algorithm. Simulation results show that the proposed optimization algorithm can outperform other methods in a set of benchmark functions. This chemical reaction optimization paradigm is also applied to solve the tracking problem for the dynamic model of a unicycle mobile robot by integrating a kinematic and a torque controller based on fuzzy logic theory. Computer simulations are presented confirming that this optimization paradigm is able to outperform other optimization techniques applied to this particular robot application.
Introduction -- Theory and Background -- Chemical Definitions -- The Proposed Chemical Reaction Algorithm -- Application Problems -- Simulation Results -- Conclusions.
Keywords: Engineering; Chemistry, Physical and theoretical; Artificial intelligence; Computational intelligence; Control engineering; Robotics; Automation; Engineering; Computational Intelligence; Control; Theoretical and Computational Chemistry; Robotics and Automation; Artificial Intelligence (incl. Robotics).; Electronic books